Avalanche Analysis of Variant Polynomials for AES - Kouther Fahad Alshammari, Ayman Mostafa, Shadi Nashwan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Advanced Encryption Standard (AES) is the most commonly used symmetric cipher nowadays. An AES cryptosystem chooses a specific irreducible polynomial to compute its values. All computations of the cryptosystem are based on this chosen polynomial. The selection of the polynomial creates the interesting opportunity to see how the cryptosystem performs when the polynomial is replaced by other irreducible polynomials. The objective of this paper is to examine the impact on the avalanche level when utilizing other polynomials to develop AES cryptosystems. To implement those AES cryptosystems easily, MATLAB® codes were written for creating 30 different AES cryptosystems. Then, the avalanche analysis was conducted on all the cryptosystems created. The results of the analysis show that choosing different polynomials as a component of the AES cryptosystems has a minor impact on the avalanche level.